Espacios intermedios y dinámicas vecinales: entre el mercado de barrio y el comercio ambulatorio en Lima Norte - Mayorca Huamán, Judit Liliana (2025)
In Lima Norte, markets in popular neighborhoods and their adjacent streets with informal commerce configure an 'intermediate space', understood as a transitional zone between these two poles where commercial and neighborhood dynamics converge. However, these neighborhood dynamics that occur within the 'intermediate space' have not been considered in the architectural design of the market or in urban interventions between the neighborhood market and the adjacent streets with informal commerce. This research seeks to analyze intermediate spaces through three approaches: architectural, urban morphological, and socio-functional. The study is based on three case studies and employs a qualitative methodology, including observation, document review, and interviews with neighbors, users, and vendors. As a result, various typologies of intermediate spaces are identified, which vary depending on the type of market and vending stall. These findings provide a basis on potential urban and architectural interventions that can be implemented.